Space and time-resolved optical emission spectroscopy in TEA-CO2 laser ablation of polymers and graphite - Siew, , WO; Wong,, KH; Yap, , SS; Tou, , TY (2005)
The luminous plumes from the TEA-CO2 laser ablation of polymethylmethacrylate, polyimide, polyethylene terepthalate, and graphite in helium were characterized by using gated optical emission spectroscopy that measured the spatial-temporal distribution of singly ionized carbon species, and also by streak photography that examined the dynamics of the propagation of the luminous plumes. The plume splitting was implicated by the fast and slow components of plume species in curve-fitting their spatial-temporal distribution with the shifted Maxwell-Boltzmann distribution function. The best-fit velocities of the fast components were confirmed by the streak photographs.